Issues and challenges in Muslim cemetery management (MCM) in Malaysia - Mohamad Daud, Noor Shafiqah; Sulaiman, Noralfishah; Anjang Ahmad, Mustaffa
Cemetery needs is a basic facility that is as important as other basic facilities to the communities in Malaysia particularly to Muslim society. Recently, a lot of issues arise in Muslim Cemetery Management (MCM) caused by increase in human population and development booming. Land shortage for burials is one of the many issues that emerge out of accelerated urban growth in most developing Asian countries, including Malaysia. Furthermore, cemetery problem is not systematically managed causing the community become uninterested to make a visit and this support superstitions mentality among the community. Thus, this paper examines problems that arise from the traditional practices of Muslim funerary as well as raises other important issues and challenges when planning for the land use needs of the dead. This paper will also provide some recommendations that can be applied to counter the existing issues